Automatic machine-aided support for English writing for Chinese students - Chua, Wee Meng. (2011)
English essay writing can be challenging for many students, especially those who speak English as a second language. However, it is an important component in English examinations, and candidates cannot afford to neglect it. Due to it being the best way of assessing a student’s command of the English language, the essay section usually take up a significant portion of the total marks.